Genius Training Center / Nora Ashikin Abd Karim ... [et.al] - Nora Ashikin, Abd Karim; Murniza, Abdul Kahar; Ermawatt, Sobri (Malaysian Entrepreneurship Development Centre (MEDEC), 2002)
We intend to set up a business of services sector that specialize in training centre named 'Genius Training Centre'. We agree to set up our businesrat-Section 13, Shah Alam Selangor. And we plan to commence our business on 1st January 2005. Our business provides motivation services for primary and secondary students, especially for students who will sit for UPSR, PMR and SPM examination. We motivate them by giving motivation talk. For example talk about how to study efficiently, how to cope with pressure during examination, time management and on self - management. The objective of our talk is to increase the awareness among the student about the importance of knowledge in our life. Besides that, our business also provide outdoor activities for student. The purpose of the activity is to build inner strength among the students. The outdoor activity that we provide is jungle tracking, camping and abseiling. Moreover, we also train students to be able to communicate well and express their feeling through ' Kaunseling Kelompok'. In this activity the students will be exposed about the communication skill, human relation skill and how to speak in front of public. We choose this business because its potential to succeed in this business is greater than the other business. Not many people interested to involve in this kind of business, so the degree of competitiveness in this business is low. Nowadays, as life is more challenging, human will always need motivation in their life in order to equip him or herself in facing any barriers. That is why we choose to venture in this business.